Interprofessionality in the health professions in the transformation of a modern role and profession development. Report on the results of a world café at the Drei-Länder-Tagung on May 5, 2022 in Bern / Interprofessionalität in den Gesundheitsberufen im Wandel einer modernen Rollen- und Professionsentwicklung. Bericht über die Ergebnisse eines World Cafés auf der Drei-Länder-Tagung am 5. Mai 2022 in Bern - Brandes Cindy; Glässel Andrea; Raab Anja; Herrmann Beate; Höppner Heidi (Sciendo, 2022)
The health professions in the German-speaking region of Germany, Austria and Switzerland, the so-called D-A-CH area, are in dynamic phases of their professionalization due to their shift towards education at universities. In addition, the needs of current and future health care require all health professionals (HPs) to have collaborative competencies and a willingness to work together. This willingness and the challenge of co-creation of health systems by all health professionals is a good starting point for the evolution of the professions. So what must professional profiles, role beliefs - in short, modern professionalization strategies - be like so that, at the beginning of the 21st century, education and professional practice do not remain stuck in old thought structures and templates and in monodisciplinary "silo thinking." What does it mean in concrete terms for the professionalization of professions that health care professions must (be able to) increasingly work together? Doesn't professionalization so far tend to mean exclusivity and isn't a stronger demarcation between the professions then the consequence? Against the background of professionalization through academization, do university studies not tend to aim at a stronger demarcation from other disciplines and professions? Professionalization includes exclusive competencies and specialized methods against the background of one's own profession-related action sciences. At the three-country meeting of the VFWG in Bern on 5-6 May 2022, this area of tension was put up for discussion in a World Café based on four theses. The following article documents the results of the individual discussion rounds and aims to stimulate a critical discourse